Implementasi Sistem Informasi Geografis dalam Pemetaan Kejadian ISPA di Wilayah Kerja Puskesmas Cipatat - Fitriani, Winda Syahrian; Firmansyah, Yura Witsqa (Jurusan Pendidikan Geografi Universitas Negeri Manado, 2025)
Cases of ARI disease in the Cipatat Health Center working area in December 2023-February 2024 are still high with 1,298 cases and no ARI disease mapping has been done. This study aims to determine the autocorrelation of prevalence, distribution patterns, number of cases, point prevalence rate value and distribution of ARI disease in the Cipatat Health Center working area. This type of research is correlation with a spatial approach based on the Moran index and with a retrospective cohort study. The data collection technique was purposive sampling, namely files taken in December 2023-February 2024 with the highest number of cases in Citatah village with 598 cases. The highest point prevalence rate value is in Citatah village with 360, the distribution is done with four-level clustering with the highest level of cases in Citatah and Cipatat villages. Based on spatial statistics, the p-value is 0.00, the hypothesis H1 is accepted and H0 is rejected because the p-value is less than α (5%). Factors causing ARI are internal community factors and external environmental factors. It can be concluded that the incidence of ARI in the Cipatat Health Center working area is cluster-shaped, which means that there are similarities in the characteristics of the incident area with other areas so that regional-based disease prevention interventions are needed.